CD4+ Resident Memory T Cells Mediate Long-Term Local Skin Immune Memory of Contact Hypersensitivity in BALB/c Mice - Murata, Akihiko; Hayashi, Shin-Ichi (Frontiers in Immunology, 2020)
In allergic contact dermatitis (ACD) and contact hypersensitivity (CHS), healed skin shows greater swelling than naïve skin in the same individual upon re-exposure to the same hapten. This ‘local skin memory (LSM)’ in healed skin was maintained for a prolonged period of time and mediated by skin CD8+-resident memory T (TRM) cells in C57BL/6 mice. However, the number of CD4+ T cells is elevated in ACD-healed human skin, and the contribution of CD4+ TRM cells to the formation of LSM currently remains unclear. We herein demonstrated that immediately after CHS subsided, healed skin in BALB/c mice showed the accumulation of hapten-specific CD4+ and CD8+ TRM cells, with a predominance of CD4+ TRM cells. The presence of CD4+ or CD8+ TRM cells in healed skin was sufficient for the induction of a flare-up reaction upon a re-challenge. CD4+ and CD8+ TRM cells both produced interferon-γ and tumor necrosis factor early after the re-challenge. Moreover, while CD8+ TRM cells gradually decreased over time and were eventually lost from healed skin 40-51 wks after the resolution of CHS, CD4+ TRM cell numbers remained elevated during this period. The present results indicate that the long-term maintenance of LSM is mediated by CD4+ TRM cells, and, thus, CD4+ TRM cells are an important target for the treatment of recurrent human ACD.